ETIKA BISNIS E-COMMERCE BERDASARKAN MAQASHID SYARIAH PADA MARKETPLACE BUKALAPAK.COM - Lailatul Maskhuroh; M. Dihyatul Fadl’laa (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
Islam has regulated all aspects of human life, and one of them is e-commerce. During the development, the number of criminals also increases. This is because of a lot of violence in business ethics that is not aware of the five basic principles of life; religion, soul, descendants, logic, and wealth (maqashid sharia). This research aims to determine the implementation of business ethics and the implementation of maqashid sharia in Bukalapak.com. This research is using a qualitative approach. To study the content, the writer analyzed the collected information through some events registered on the website of Bukalapak.com. The conclude this research is the implementation of business ethics has been done well as applied by Rasulullah SAW, as in maqashid sharia with four protection system has been applied to protect the rights of the customers. This research recommends that all regulations should be applied well. It is also necessary to make a board to control any transaction of e-commerce to meet the principles of sharia and the regulation